News media literacy and conspiracy theory endorsement. Issue 4 (December 2017) - Craft, Stephanie; Ashley, Seth; Maksl, Adam
Conspiracy theories flourish in the wide-open media of the digital age, spurring concerns about the role of misinformation in influencing public opinion and election outcomes. This study examines whether news media literacy predicts the likelihood of endorsing conspiracy theories and also considers the impact of literacy on partisanship. A survey of 397 adults found that greater knowledge about the news media predicted a lower likelihood of conspiracy theory endorsement, even for conspiracy theories that aligned with their political ideology.